Vernacular architecture in eastern Senegal: Chaînes opératoires and technical choices. (September 2020) - Pelmoine, Thomas; Mayor, Anne
Architecture is an important component of cultural identity, but knowledge regarding construction techniques using local materials is gradually disappearing, and this subject has rarely been studied in sub-Saharan Africa. This ethno-archaeological study of current vernacular architecture and its evolution during the past three centuries in eastern Senegal therefore brings innovative results that are interesting on different levels. In relation to West Africa, the authors aim to provide new knowledge useful for archaeologists lacking references for interpreting past remains, as well as an archive for historical and heritage studies. More widely, the study constitutes a reference for the description of various mud-building techniques and an attempt to understand the mechanisms explaining their transformations, which should concern all scientists interested in vernacular architecture, in Africa and beyond. More precisely, this article accounts for the variability of techniques used for constructing walls and roofs of dwellings in the Faleme valley among different ethno-linguistic groups, while considering the environmental, cultural and socio-economic factors at play. The authors' methodology is based on a description of the chaînes opératoires of construction, interviews, mapping and statistical analysis. The patterns observed facilitate a discussion on the evolution of techniques, environmental adaptations, the transfer of knowledge and the role of history in material culture dynamics.